2004
DOI: 10.1209/epl/i2003-10132-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized criticality in the Bean state in YBa 2 Cu 3 O 7 − x thin films

Abstract: The penetration of magnetic flux into a thin film of YBa2Cu3O7−x is studied when the external field is ramped slowly. In this case the flux penetrates in bursts or avalanches. The size of these avalanches is distributed according to a power law with an exponent of τ = 1.29(2). The additional observation of finite-size scaling of the avalanche distributions, with an avalanche dimension D = 1.89(3), gives strong indications towards self-organized criticality in this system. Furthermore we determine exponents gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…A similar value ͑ = 1.09͒ has been obtained recently by Radovan and Zieve 28 in Pb plain films by analyzing the size of the magnetization jumps using local Hall probe measurements. For YBa 2 Cu 3 O 7 Aegerter et al, 30 found a slightly larger value = 1.29͑2͒. It is important to mention that the different behavior of avalanche size distribution, as reported in other systems, 31,32 could be due to the characteristics of the quenched disorder potential present in each case.…”
Section: Avalanche Size Distributionmentioning
confidence: 83%
“…A similar value ͑ = 1.09͒ has been obtained recently by Radovan and Zieve 28 in Pb plain films by analyzing the size of the magnetization jumps using local Hall probe measurements. For YBa 2 Cu 3 O 7 Aegerter et al, 30 found a slightly larger value = 1.29͑2͒. It is important to mention that the different behavior of avalanche size distribution, as reported in other systems, 31,32 could be due to the characteristics of the quenched disorder potential present in each case.…”
Section: Avalanche Size Distributionmentioning
confidence: 83%
“…SOC was first introduced by Bak, Tang and Wiesenfeld [3] as an explanation for the power-law behavior observed in some natural processes such as 1=f noise or avalanches in sandpiles. Since then, many theoretical and numerical models have been shown to exhibit SOC [2,4] but few physical realizations have been identified [2,[5][6][7][8][9][10]. An interesting path to SOC has been explained for systems exhibiting a nonequilibrium phase transition between fluctuating ''active'' steady states and nonfluctuating ''absorbing'' states from which the system cannot escape [2].…”
mentioning
confidence: 99%
“…However, progress has been hampered by the fact that clear, tell-tale signs of criticality, such as finite-size scaling in the distribution of avalanches, have only been observed in very few controlled experiments [4]. Recently however, there have been a number of experimental observations of criticality in both two- [5,6] and three dimensional systems [7][8][9]. However, the critical ingredients to obtain SOC in an experimental system still remain obscure.…”
mentioning
confidence: 99%
“…As first noted by de Gennes [15], the penetration of a slowly ramped magnetic field into a type-II superconductor has a strong analogy to the growing of a sand pile, the archetypal example of SOC. It has been shown in the past, that these vortex avalanches are distributed according to a power-law [16] and more recently that they obey finite-size scaling [9]. However, due to the presence of pinning in the system, studying magnetic vortices allows a detailed investigation of the influence of quenched disorder on their avalanche distribution and structure.…”
mentioning
confidence: 99%